2003
DOI: 10.1021/ja036006g
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effects on Hydrophobic Interactions:  The Importance of Dispersion Interactions in the Hydrophobic Phase

Abstract: Hydrogen/deuterium isotope effects on hydrophobic binding were examined by means of reversed-phase chromatographic separation of protiated and deuterated isotopologue pairs for a set of 10 nonpolar and low-polarity compounds with 10 stationary phases having alkyl and aryl groups bonded to the silica surface. It was found that protiated compounds bind to nonpolar moieties attached to silica more strongly than deuterated ones, demonstrating that the CH/CD bonds of the solutes are weakened or have less restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
163
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 69 publications
14
163
1
2
Order By: Relevance
“…These factors could in principle lead to a change of non-covalent (for example, hydrogen bonding, CH-p, p-p, and cation-p) interactions upon deuteration. There have been a few studies in the past showing that deuteration of C-H oscillators can lead to decreased non-covalent interactions in a non-conjugated system, but the observed differences were too small to be statistically significant, and the exact causality could therefore not be established unambiguously [5][6][7][8] .…”
mentioning
confidence: 99%
“…These factors could in principle lead to a change of non-covalent (for example, hydrogen bonding, CH-p, p-p, and cation-p) interactions upon deuteration. There have been a few studies in the past showing that deuteration of C-H oscillators can lead to decreased non-covalent interactions in a non-conjugated system, but the observed differences were too small to be statistically significant, and the exact causality could therefore not be established unambiguously [5][6][7][8] .…”
mentioning
confidence: 99%
“…[13][14][15] They showed that the 3-(pentabromobenzyloxy)-propyl (PBB) group immobilizes silica (PBB-silica) and had a high specificity for halogenated benzenes based on the dispersibility. The separation factors α value calculated from the retention factors of dihalogenated benzenes and p-xylene on the DBP-resin in this study were all larger than those reported for the PBB-silica in the previous study (Table 2).…”
Section: Retention Of Halogenated Aromatics On Dbp-resin and Pbbsilicamentioning
confidence: 99%
“…Tanaka and coworkers [13][14][15] developed several silica stationary phases immobilized with halogenated aromatic rings to examine the dispersibility of heavy atoms. These columns were used to separate fullerene isomers, halogenated compounds and deuterium compounds.…”
mentioning
confidence: 99%
“…However, it has to be noted that some physical properties, such as the molecule's dispersion forces, are also slightly changed by the deuteration. 23,24 By now, various behavioural studies of isotopomer discrimination were performed in humans, [24][25][26] in Drosophila, 20,27 and in honeybees. 28 While outcomes of human tests were mixed, insect behavioural tests showed isotopomer discrimination.…”
Section: Introductionmentioning
confidence: 99%